b y Connie and Peter Roop ; illustrated by Carol Schwartz. - Roop, Connie; Schwartz, Carol, 1954- (New York : Scholastic, 2006)
Simple rhyming text describes the characteristics and behavior of starfish.
Text in Arabic.
K-3
Translation of: Starfish : stars of the sea.
Title supplied by OCLC WorldCat.
Keywords: Starfishes -- Juvenile literature; Starfishes; Arabic language materials; Starfishes; Arabic language